Immunological routine laboratory parameters at admission influence the improvement of positive symptoms in schizophrenia patients after pharmacological treatment - Skalniak, Anna; Krzyściak, Wirginia; Śmierciak, Natalia; Szwajca, Marta; Donicz, Paulina; Kozicz, Tamas; Pilecki, Maciej (Frontiers in Psychiatry, 2023)
The standard care of schizophrenia patients is based on the assessment of their psychotic behavior, using interview-based, subjective scales that measure symptom severity. We aimed at defining easily accessible and inexpensive blood-derived clinical diagnostic parameters that might serve as objective markers in the prediction of the effects of pharmacological treatment of schizophrenia patients. 40 patients with schizophrenia diagnosis according to ICD 10 during psychotic decompensation were included in the study. Blood-based biochemical parameters, BMI, and interview-based medical scales of symptom severity were determined - all at admission and after 12 weeks of standard pharmacological treatment. The drops in scale values were correlated with clinical parameters. All scale changes after treatment were dependent on the value of the given scale at admission, with higher initial values leading to larger drops in the values after treatment. Models based on those correlations were significantly improved when immune and metabolism parameters were included. C4 complement and C-reactive protein (CRP) levels at admission were predictive of changes in Positive and Negative Syndrome Scale (PANSS) subscales related to significant disruption of thought processes, reality testing, and disorganization. The pharmacological treatment-driven changes in scales representing negative symptoms were correlated with markers of the patient's thyroid status and metabolism. We show that objective markers can be obtained by testing immune and metabolic parameters from the patients’ blood and may be added at a low cost to the standard care of schizophrenia patients in order to predict the outcome of pharmacological treatment.